2016
DOI: 10.1177/0310057x1604400308
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Observational Study of the Association between Cabin and outside Air Temperature, and Patient Temperature Gradient during Helicopter Transport in New South Wales

Abstract: The prevalence of hypothermia in patients following helicopter transport varies widely. Low outside air temperature has been identified as a risk factor. Modern helicopters are insulated and have heating; therefore outside temperature may be unimportant if cabin heat is maintained. We sought to describe the association between outside air, cabin and patient temperature, and having the cabin temperature in the thermoneutral zone (18-36 o C) in our helicopter-transported patients. We conducted a prospective obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 20 publications
0
11
1
Order By: Relevance
“…Just under one quarter (23.6%) of body temperatures that were recorded at destination were ≤35 C, while a comparable service in the UK found similar rates of hypothermia among adult burns patients (19%). 15 A high proportion of interhospital patients were found to be hypothermic prior to transport (32%) in another recent publication by GSA-HEMS, 16 which may account for some of these findings; however, it may be that hypothermia is a complication of burns more common to retrieval medicine. A European study of pre-hospital burns care demonstrated that each drop in temperature by 1 C significantly increases mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Just under one quarter (23.6%) of body temperatures that were recorded at destination were ≤35 C, while a comparable service in the UK found similar rates of hypothermia among adult burns patients (19%). 15 A high proportion of interhospital patients were found to be hypothermic prior to transport (32%) in another recent publication by GSA-HEMS, 16 which may account for some of these findings; however, it may be that hypothermia is a complication of burns more common to retrieval medicine. A European study of pre-hospital burns care demonstrated that each drop in temperature by 1 C significantly increases mortality.…”
Section: Discussionmentioning
confidence: 99%
“…We divided T before and T after into three groups: hyperthermia (N38.0°C ), normothermia (36.0-37.9°C), and hypothermia (b36.0°C) [4]. The following patient categories described body temperature change: hypothermia both before and after air transport ("hypo to hypo"); hypothermia before air transport and normothermia after air transport ("hypo to normo"); hypothermia before air transport and hyperthermia after air transport ("hypo to hyper"); normothermia before air transport and hypothermia after air transport ("normo to hypo"); normothermia both before and after air transport ("normo to normo"); normothermia before air transport and hyperthermia after air transport ("normo to hyper"); hyperthermia before air transport and hypothermia after air transport ("hyper to hypo"); hyperthermia before air transport and normothermia after air transport ("hyper to normo"); and hyperthermia both before and after air transport ("hyper to hyper").…”
Section: Data Collectionmentioning
confidence: 99%
“…For example, one emergency medical center in our region conducts air medical transport for approximately 250 patients a year from isolated islands. Distances range from 100 to 1000 km, and transport usually takes from 30 min to 5 h. These flights cover longer distances and require longer duration than those in previous studies [1][2][3][4]6].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations